Rendering interactive 3D scene as a web-page using Three.js, WebGL, and Blender - Bose, Sudeepto (Brac University, 2023)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Computer Science, 2022.